Pengembangan Iman Anak Melalui Pendidikan Agama Berbasis Pengalaman dalam Komunitas - Hermawan Winditya (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
The purpose of this study is to present experience-based religious education in the community as an alternative that is worth considering juxtaposed with religious education which tends to emphasize cognitive aspects. This experience-based religious education provides a strong foundation for children in facing challenges in this increasingly advanced and modern era, such as materialism, secularism, and hedonism. The method used is a library study related to the experience-based model of religious education in the community. The results of a study of the implementation of experiencebased religious education in the community show that this learning model is more fun for children because it is contextual to the lives of children in their families, schools, and communities. Conclusion Experience-based religious education in this community further develops children's faith and is fun for children, thus enabling children to develop as a whole, both cognitive, affective, and psychomotor.